Frontispiece: Superamphiphilic Silicon Wafer Surfaces and Applications for Uniform Polymer Film Fabrication. Issue 21 (15th May 2017) - Zhu, Zhongpeng; Tian, Ye; Chen, Yupeng; Gu, Zhen; Wang, Shutao; Jiang, Lei
Abstract : Surface Chemistry In their Communication onpage 5720 ff., Y. Tian and co‐workers report the generation of super‐amphiphilic silicon wafer surfaces with alternating hydrophilic/hydrophobic nanodomains, upon which uniform polypyrrole films can be formed.